Kekayaan Spesies Kelelawar Ordo Chiroptera Di Gua Wilayah Selatan Pulau Lombok, Nusa Tenggara Barat - Siti Rabiatul Fajri; Agil Al Idrus; Gito Hadiprayitno (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2014)
The research was conducted in order to determine the species richness in the cave region of southern island of Lombok. The study was conducted through a survey technique at 5 caves located in the southern region of the island of Lombok the Cave Gale-Gale, Buwun Cave, Cave Kenculit, Raksasa Cave and Cave Pantai Surga. The survey was conducted from March to May 2014. Sampling bat for identification as done by using the mist nets. Bats were caught identified further in the Laboratory of Biological Science, University of Mataram. The results show that has found 6 Family with 12 species. Based on identification of 12 species were found in the caves of the area south of the island of Lombok, there are 9 species ever discovered by Kitchener (2002) in his study on the island of Lombok is Hipposiderosater, Rhinolopussimplex, Rosettusamplxicaudatus, Hipposiderosdiadema, Eonycterisspeleae, Miniopteruspusillus, Taphazousmelanopogon, Macroglossusminimus, and Murinacyclotis, Hipposiderosbicolor, Rhinopoma microphyllum and Phoniscus atrox.